Tìm x,biết 5/4 + x =-1/8.x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: x=3/4-1/2=3/4-2/4=1/4
2: x-1/5=2/11
=>x=2/11+1/5=21/55
3: x-5/6=16/42-8/56
=>x-5/6=8/21-4/28=5/21
=>x=5/21+5/6=15/14
4: x/5=5/6-19/30
=>x/5=25/30-19/30=6/30=1/5
=>x=1
5: =>|x|=1/3+1/4=7/12
=>x=7/12 hoặc x=-7/12
6: x=-1/2+3/4
=>x=3/4-1/2=1/4
11: x-(-6/12)=9/48
=>x+1/2=3/16
=>x=3/16-1/2=-5/16
1)x= 1/4
2)x= 2/11+ 1/5
x= 21/55
3)x - 5/6 = 5/21
x = 5/21+5/6
x = 15/14
4)x/5 = 5/6 + -19/30
x:5 = 1/5
x = 1/5.5
x = 1
5) |x| - 1/4 = 6/18
|x| = 6/18 - 1/4
|x| =7/12
⇒x= 7/12 hoặc -7/12
6)x = -1/2 +3/4
x= 1/4
7) x/15 = 3/5 + -2/3
x:15 = -1/15
x = -1/15. 15
x = -1
8)11/8 + 13/6 = 85/x
85/24 = 85/x
⇒ x = 24
9) x - 7/8 = 13/12
x = 13/12 + 7/8
x = 47/24
10)x - -6/15 = 4/27
x = 4/27 + (-6/15)
x = -34/135
11) -(-6/12)+x = 9/48
x= 9/48 - 6/12
x = -5/16
12) x - 4/6 = 5/25 + -7/15
x -4/6 = -4/15
x = -4/15 + 4/6
x = 2/5
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(\dfrac{8}{7}-\dfrac{1}{7}:\left(\dfrac{x}{3}-2\right)=-1\)
\(-\dfrac{1}{7}:\left(\dfrac{x}{3}-2\right)=\dfrac{15}{7}\)
\(\dfrac{x}{3}-2=\dfrac{-1}{15}\)
\(\dfrac{x}{3}=\dfrac{29}{15}\)
\(x=5,8\)
b. \(\dfrac{5}{8}+\dfrac{1}{4}\left(2x-1\right)=\dfrac{5}{4}\)
\(\dfrac{1}{4}\left(2x-1\right)=\dfrac{5}{8}\)
\(2x-1=\dfrac{5}{2}\)
\(2x=\dfrac{7}{2}\)
\(x=\dfrac{7}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 2x+\(\dfrac{4}{5}\)=0 hoặc 3x-\(\dfrac{1}{2}\)=0
2x=- 4/5 hoặc 3x=1/2
x=-2/5 hoặc x=\(\dfrac{1}{6}\)
b. x-\(\dfrac{2}{5}\)=0 hoặc x+\(\dfrac{4}{7}\)=0
x=2/5 hoặc x=-\(\dfrac{4}{7}\)
d. x(1+5/8-12/16)=1
\(\dfrac{7}{8}\)x=1=> x=8/7
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{1}{4}x-1\right)+\left(\frac{5}{6}x-2\right)-\left(\frac{3}{8}x+5\right)=3,5\)
\(\Rightarrow\frac{1}{4}x-1+\frac{5}{6}x-2-\frac{3}{8}x-5=\frac{7}{2}\)
\(\Rightarrow\left(\frac{1}{4}+\frac{5}{6}-\frac{3}{8}\right)x+\left[\left(-1\right)+\left(-2\right)+\left(-5\right)\right]=\frac{7}{2}\)
\(\Rightarrow\frac{17}{24}x+\left(-8\right)=\frac{7}{2}\)
\(\Rightarrow\frac{17}{24}x=\frac{7}{2}-\left(-8\right)=\frac{23}{3}\)
\(\Rightarrow x=\frac{23}{2}:\frac{17}{24}=\frac{276}{17}\)
~ Hok tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
1: =>x=3/5-1/5=2/5
b: =>x/3=5/8+1/8=3/4
=>x=9/4
3: =>10/3x=3+1/4+6+3/4=10
=>x=10:10/3=3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
`x-3/5 =-4/10`
`=>x=-4/10 + 3/5`
`=>x=-4/10 + 6/10`
`=>x= 2/10`
`=>x=1/5`
`----`
`(x-1)/(-2) = -8/(x-1)`
`=> (x-1).(x-1) = (-2).(-8)`
`=> (x-1)^2 = 16`
`=> (x-1)^2 = +- 4^2`
\(\Rightarrow\left[{}\begin{matrix}x-1=4\\x-1=-4\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=4+1\\x=-4+1\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=5\\x=-3\end{matrix}\right.\)
5/4+x=-1/8.x
5/4=-1/8.x-x
5/4=(-1/8-1).x
5/4=-8/9.x
x=5/4:-8/9
x=19/8
\(\dfrac{5}{4}+x=-\dfrac{1}{8}x\)
=>\(-\dfrac{1}{8}x-x=\dfrac{5}{4}\)
=>\(-\dfrac{9}{8}x=\dfrac{5}{4}\)
=>\(x=\dfrac{5}{4}:\dfrac{-9}{8}=\dfrac{5}{4}\cdot\dfrac{8}{-9}=\dfrac{-10}{9}\)